Processing of chip and small-scale wastes of aluminum alloys - M. A. Sadokha; B. A. Kraev; V. I. Gutko; A. I. Gutko (Литьë и металлургия, 2001)
The stages of processing of chip and smali-scaie wastes of aluminum alloys are described.